Carbohydrate intolerance - V. O. Kaybysheva; Ye. K. Baranskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To present the modern concept on etiology and pathogenesis of food intolerance, to analyze the modern strategy of diagnosis and treatment of carbohydrate intolerance. Key points. Patients, who presented with abdominal pain, diarrhea, flatulence at the absence of organic diseases should be investigated to exclude intolerance of nutritional components, first of all - carbohydrates. If food intolerance was confirmed, high performance treatment methods should be applied including dietary modification with elimination of intolerable food products, addition of specific enzyme preparations to the treatment mode. Conclusion. Carbohydrate intolerance results in abdominal pain, flatulence and diarrhea in generally healthy population and patients with functional gastrointestinal diseases. Early detection of integrated agentт and its elimination from the ration will provide significant decrease in symptom severity.